The Study And Function of Software Sibelius: : Audio Score Number Converted To Partitur Score In Ave Maria 'S Song In Lourdes Madah Bakti -546 - pernandus simanullang (Institut Agama Kristen Negeri Manado, 2022)
Nowadays, life activists are inseparable from technological advances, everything they cannot be separated from the help of improving this advanced study to see and examine the function of software on Sibelius, Sibelius, not numbers converted to block notes. The musicians still use manual to convert these scores, because they are not used to using digital patterns. Sibelius' software makes it easy for music conductors or creators to explore their inspiration. The explanation of Sibelius and the notation of numbers are indeed important for musicians who are not yet friendly to him. This research method uses descriptive qualitative, examining a previous explanation to see the similarities and, advantages, and disadvantages of number notation and block notation. Examines the extent to which Sibeliuscanis able to read its conversions.